Guideline for improving capacity of a job shop based on selected performance measures - Salehun, Md Amirul Khair; Md. Tap, Masine; Mohamed Shaharoun, Awaluddin (Penerbit UTM Press, 2005)

(untitled)
Manufacturing companies are required to fulfill customer’s driven imperatives such as on time delivery as well its own requirements such as high machine utilisation and low work in process. In order to achieve these, manufacturers need to adopt the right manufacturing strategy. Selecting the right manufacturing strategies will improve its capability to meet its customers demand as well as its ovvn limitations. This research identifies five strategies that a job shop may adopt to achieve flexibility in meeting demand. The five strategies ranges from the basic strategy of having a complete set of single–operation machines to flexible multi–operation machines. Each strategy is evaluated and a set of guideline is proposed. The results show that when job tardiness and work–in–process is the performance criteria, the duplication strategy is the best. However, if the performance criteria is machine utilisation, then the best strategy is the replacement strategy.